Effect of Nutrient Addition on the Productivity and Species Richness of Grassland Along With an Elevational Gradient in Tajikistan - Fan, Lian-Lian; Mekrovar, Okhonniyozov; Li, Yao-Ming; Li, Kai-Hui; Ma, Xue-Xi; Mao, Jie-Fei (Frontiers in Plant Science, 2021)
Grasslands provide a key resource for the millions of people who are dependent on livestock in Tajikistan. Productivity and species richness are important characteristics of grassland ecosystem while nutrient has an important limitation effect on them. However, the dynamics of those characteristics become uncertain with climate change. Therefore, the in-situ nitrogen (N) and phosphorus (P) fertilization experimental manipulation along elevational gradients (650 m, 1100 m, 1250 m and 2000 m) in west Tajikistan were conducted to examine the influences of nutrient availability on aboveground biomass (AGB) and species richness (SR) during the year from 2018 to 2019. CK- as the control, N3- adding 30kgN ha-1year-1, P3 - adding 30kgP ha-1·year-1, N3P3 - adding 30kgN and 30kgP ha-1·year-1, N9P3- adding 90kgN and 30kgP ha-1·year-1, precipitation and temperature were also considered to analyze the responses. It demonstrated that, the nutrient enrichment significantly increased AGB both in 2018 and 2019 along elevational gradients (p < 0.05). The more nutrient addition, the higher AGB, the maximum AGB occurred under N9P3 treatment which increased AGB nearly by 2 times compared with control. In addition, Nitrogen addition alone is more conducive to plant growth than phosphorus addition alone. The decrease of SR after nutrient addition may be the result of plant nutrient competition. The elevation changes directly cause the variation of precipitation and temperature, thus resulting in AGB variation along elevational gradients. Precipitation mainly determined the AGB at mid-lower elevation grassland, however, temperature was a stronger driver than precipitation at high elevation grassland. Moreover, In the high elevation area, nutrient addition had insignificant effect on SR, while in the mid-low elevation area, the change of SR between different years may be regulated by precipitation.